2018
DOI: 10.1021/acschemneuro.8b00253
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Based Acetylcholinesterase Inhibitor Crosses the Blood-Brain Barrier and Promotes Neuroprotection

Abstract: Design and development of acetylcholinesterase (AChE) inhibitor has tremendous implications in the treatment of Alzheimer's disease (AD). Here, we have adopted a computational approach for the design of a peptide based AChE inhibitor from its active site. We identified an octapeptide, which interacts with the catalytic anionic site (CAS) of AChE enzyme and inhibits its activity. Interestingly, this peptide also inhibits amyloid aggregation through its interaction at the 17-21 region of amyloid-beta (Aβ) and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…Complete understanding of the apoptosis regulatory network will unravel new possibilities to interfere with dysregulated or disease-activated pathways. Some natural compounds [ 33 ] and synthetic molecules [ 23 ] that interfere with AChE functions have already been demonstrated to prevent apoptotic cell death. Potential use of cell-protective drugs in degenerative diseases could be explored also with support of knowledge gained from insects and other invertebrate species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complete understanding of the apoptosis regulatory network will unravel new possibilities to interfere with dysregulated or disease-activated pathways. Some natural compounds [ 33 ] and synthetic molecules [ 23 ] that interfere with AChE functions have already been demonstrated to prevent apoptotic cell death. Potential use of cell-protective drugs in degenerative diseases could be explored also with support of knowledge gained from insects and other invertebrate species.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, AChE is known to terminate synaptic transmission at cholinergic synapses by hydrolytic cleavage of the transmitter acetylcholine. However, other non-canonical functions of AChE in cell growth, cellular differentiation, cell adhesion and amyloid fiber assembly (amongst others) have been reported [22][23][24]. Vertebrates express a single AChE gene by different cell types in various tissues either constitutively or stimulusinduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mondal et al. () identified an octapeptide (Asn‐Phe‐Arg‐Val‐Leu‐Thr‐Lys‐Gln), which exerts AChE inhibitory activity by binding to the catalytic anionic site of AChE enzymes. Therefore, peptides with benzyl and phenyl rings exert AChE inhibitory activity; in addition, peptides can inhibit AChE function by interacting with an active site (Figure ).…”
Section: Mechanism Of Neuronal Cell Death and The Effects Of Peptidesmentioning
confidence: 99%
“…In addition, a few reports have suggested that small substituents in the benzyl ring and phenyl ring enhance AChE inhibitory activity (Ali, Yar, Hasan, Ahsan, & Pandian, 2009;Korabecny et al, 2014). Mondal et al (2018) identified an octapeptide (Asn-Phe-Arg-Val-Leu-Thr-Lys-Gln), which exerts AChE inhibitory activity by binding to the catalytic anionic site of AChE enzymes. Therefore, peptides with benzyl and phenyl rings exert AChE inhibitory activity; in addition, peptides can inhibit AChE function by interacting with an active site ( Figure 3).…”
Section: Acetylcholinesterase Inhibitory Activitymentioning
confidence: 99%